Relationship of Open Communication to Employee Motivation in a Government Agency in the Philippines - Erika Ruth F. Larroza; Swtizel Ann G. Basilla; Ma. Angelica Casano; Jesus P. Briones; Marmelo V. Abante (Research Synergy Foundation Press, 2024)
Effective communication is essential for fostering a motivated and engaged workforce, particularly in government organizations where transparency and collaboration are vital. This study examines the relationship between open communication practices and employee motivation within a government agency in the Philippines, focusing on 129 employees from a total population of 192 in the division under the Collection Service. Employing a descriptive-correlation research design, data were gathered through a researcher-structured questionnaire and analyzed using frequency, percentage, weighted mean, standard deviation, and Pearson correlation coefficient as statistical tools. The results indicate that effective communication, particularly regarding information accessibility, improves employee engagement and performance. However, feedback mechanisms and communication frequency were identified as areas for improvement. A supportive work environment emerged as the most potent motivator, followed by recognition and career development opportunities, whereas compensation played a lesser role. This study revealed that barriers such as organizational structure and inadequate communication channels hinder effective communication. The findings also reveal a strong positive correlation between open communication and employee motivation. On the other hand, the correlation between open communication and barriers to it was weak, whereas the relationship between employee motivation and barriers to it exhibited a moderate positive correlation. The study emphasizes the importance of enhancing open communication to boost employee engagement and performance and offers strategic recommendations to address these barriers.